2015
DOI: 10.1177/1077558715606261
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Racial and Ethnic Disparities in Cardiac Rehabilitation Use

Abstract: Cardiac rehabilitation (CR) use is lower for racial and ethnic minorities than White patients. The purpose of this study was to identify factors that drive this disparity at the system, provider, and patient levels. A mixed methods study combined descriptive analysis of 2007 Medicare claims data and thematic analysis of 19 clinician interviews, 8 minority patient focus groups and 8 one-on-one interviews with minority heart patients across three communities. The disparity between White and non-White CR use rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 38 publications
(43 reference statements)
0
45
0
Order By: Relevance
“…90 Finally, the interplay between gender and ethnicity warrants further investigation, particularly because women in underrepresented minority groups experience various health care disparities, including the underutilization of CR services. 91 …”
Section: Discussionmentioning
confidence: 99%
“…90 Finally, the interplay between gender and ethnicity warrants further investigation, particularly because women in underrepresented minority groups experience various health care disparities, including the underutilization of CR services. 91 …”
Section: Discussionmentioning
confidence: 99%
“…In addition to gender disparities, racial and ethnic factors also contribute to lower CR referral and completion rates. Several studies have shown lower CR referral rates for nonwhite individuals as compared to white individuals [47][48][49]. In a study by Aragam et al, hospitals with high CR referral rates (> 90%), reported no difference in CR referrals between white vs. non-white patients [30].…”
Section: Gender and Racialmentioning
confidence: 99%
“…Second, the sample consisted of predominately-White males enrolled in a CRP, which limits the generalization of study results to racial and ethnic minorities who carry the heaviest burden of adverse cardiac events such as myocardial infarction, ischemic heart disease, and heart failure (Virani et al, 2020; Whelton et al, 2017). In contrast, while the current participation in CRP is about 20% to 30% (Ades et al, 2017), approximately 7% to 11% of racial-ethnic minorities use CRPs (Mead et al, 2016). However, African Americans, Hispanics, and Asians populations are 20%, 30%, and 50%, respectively, less likely to be referred to, participate in, or benefit from CRP (Li et al, 2018).…”
Section: Discussionmentioning
confidence: 99%